METABOLIC ALKALEMIA IN HYPERCALCIURIA STONE FORMERS: DOES IT MATTER? - Renato V. M. Starek; Samirah A. Gomes; Claudia M.B. Helou (Karger Publishers, 2024)
TThe literature lacks whether metabolic alkalemia occurs in outpatients with hypercalciuric nephrolithiasis. Thus, we aim to investigate it because these patients are often treated with thiazides to reduce urinary calcium excretion. However, thiazides induce chloride losses due to the inhibition of Na-Cl cotransporter expressed in the renal distal tubule cells. Besides thiazide prescription, many of these patients are also supplemented with potassium citrate, which is an addition of alkali source in their bodies. Methods: We collected clinical, demographic characteristics, and laboratory data from electronical medical charts of outpatients with calcium-kidney stones followed in our institution from January 2013 to July 2021. We diagnosed as metabolic alkalemia those cases in which the venous blood gas tests showed pH≥7.46 and bicarbonate concentration>26 mEq/L. Then, we applied statistical analysis to compare distinct categories between patients with and without metabolic alkalemia. Results: We diagnosed metabolic alkalemia in 4.3% of hypercalciuric nephrolithiasis outpatients, and we verified that thiazides had been used in all of them except in one case. Furthermore, we observed that the amount of thiazide taken daily was higher in patients with metabolic alkalemia than those without this imbalance. Additionally, hypokalemia was present in 37% of patients that developed metabolic alkalemia. We also found lower chloride, magnesium and ionic calcium serum concentrations in patients with metabolic alkalemia than in those without an acid-base disequilibrium. Conclusion: Despite the low prevalence of metabolic alkalemia in hypercalciuric kidney stone formers, it is important to monitor these patients due to high incidence of hypokalemia and the potential presence of other electrolyte disorders.